Podcasting as a tool for developing auditory competence in a digital educational environment - Rakhmonov, Azizkhon Bositkhonovich (The Lingua Spectrum, 2026)
The article examines the didactic potential of podcasting as a tool for developing auditory competence in a digital educational environment within Russian language instruction. The relevance of the study is determined by the digital transformation of education and the need to integrate innovative technologies into the process of forming communicative competence. The paper analyzes the theoretical foundations of auditory competence, its psychological and pedagogical mechanisms, and structural components. Special attention is paid to podcasting as a form of digital audio content characterized by authenticity, genre diversity, and communicative orientation. The main principles for selecting educational podcasts are substantiated, including communicative relevance, level appropriateness, sociocultural representation, and methodological expediency. The findings indicate that systematic use of podcasting enhances global, selective, and detailed listening skills, as well as anticipatory mechanisms and semantic interpretation of spoken texts. It is concluded that podcasting serves as an effective means of modernizing Russian language teaching methodology and fostering comprehensive communicative competence in the context of educational digitalization.